Reevaluating “First-to-File” vs the Legality Principle: Rethinking Justice for Original Rights Holders in Indonesia - Freaddy Busroh, Firman; Khairo, Fatria; Saraya, Sitta (Faculty of Law, Jambi University, 2025)
The implementation of the First-to-File principle within Indonesia’s intellectual property law system often raises concerns regarding justice—particularly for individuals or entities who originally created or utilized a work but failed to register it promptly. This study seeks to evaluate the compatibility of the First-to-File principle with the principle of legality in the protection of intellectual property rights and examines the extent to which it upholds justice for the original creator. As a juridical-normative study, the research employs qualitative methods through the analysis of legal documents, case studies, and a review of both national and international scholarly literature. It also uses Rawls’ theory of justice and Dworkin’s theory of rights to frame the analysis. Findings indicate that the strong emphasis on administrative procedures in the intellectual property registration system tends to overlook the moral and historical dimensions of ownership. This emphasis is normatively inconsistent with the principle of legality, which aspires to ensure equitable and proportionate legal protection. Furthermore, the disproportion between formalistic registration requirements and substantive justice creates opportunities for unethical exploitation. Accordingly, the study highlights the need for a reformulation of legal norms and policies to better accommodate the rights of original creators and to establish a fairer evidentiary mechanism within the registration process.